Health Literacy and Regional Heterogeneities in China: A Population-Based Study - Li, Zhenhua; Tian, Yongquan; Gong, Zhicheng; Qian, Long (Frontiers in Public Health, 2021)
Background: Health literacy is essential to population health, yet few studies have described the geographic variation in health literacy in China. This study aimed to investigate the level of health literacy, its regional heterogeneities, as well as influencing factors of health literacy in 25 provinces or municipalities in China. Methods: The study was conducted among residents aged 15–69 years from 25 provinces or municipalities in China in 2017. Health literacy was measured using the Chinese Health Literacy Scale. MapInfo software was used to map the geographic distribution. Multiple logistic regression was used to adjust for the factors associated with the health literacy level in the overall and regional samples. Results: A total of 3,482 participants were included in the study, comprising 1,792 (51.5%) males and 1,690 (48.5%) females. Notable geographic variation was observed in health literacy levels. The proportion of respondents with adequate health literacy was 22.3% overall, 33.0% in the eastern region, 23.1% in the central region, and 17.6% in the western region. The proportion of adequate health literacy in the different provinces and municipalities ranged from 10.5% (Xinjiang) to 47.0% (Beijing). Being a female [odds ratio (OR) = 1.353; 95% confidence interval (CI): 1.146–1.597], having a high education level [OR ranging from 2.794 (CI: 1.469–5.314) to 9.458 (CI: 5.251–17.036)], having a high economic status [OR ranging from 1.537 (CI: 1.248–1.891) to 1.850 (CI: 1.498–2.284)], having a good self-rated health status [OR ranging from 2.793 (CI: 1.534–5.083) to 3.003 (CI: 1.672–5.395)], and having frequent community health education (OR = 1.588; 95% CI: 1.066–2.365) were independently associated with adequate health literacy. Conclusions: The health literacy level in the 25 provinces or municipalities of China is relatively low compared to the developed countries, and there are heterogeneities among different regions, between urban and rural areas, and among different social groups. Tailored health education and promotion strategies are needed for different subgroups of residents.